2023
DOI: 10.1088/1742-6596/2533/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Non-Abelian gauge structure and flavor mixing in quantum field theory1

Abstract: The quantum field theory formalism describing the phenomenon of neutrino mixing and oscillations is reviewed in its essential aspects. The condensate structure of the flavor vacuum state is considered and its non-perturbative nature is discussed within the existence in the quantum field theory of the manifold of unitarily inequivalent representations of the anticommutation relations. The Poincaré structure of the theory is discussed in connection with the gauge theory features of neutrino mixing, where the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The variety of extant approaches includes the Majorana mass term, right-handed neutrinos with a see-saw mechanism, supersymmetric extensions of Standard model, and more. One intriguing possibility is the generation of neutrino masses and mixing via the aforementioned flavor vacuum condensate [46][47][48]. However, in the present paper we do not address the issue of the origin of neutrino masses, and focus on demonstrating the calculation of neutrino oscillations in the FTPFT framework.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The variety of extant approaches includes the Majorana mass term, right-handed neutrinos with a see-saw mechanism, supersymmetric extensions of Standard model, and more. One intriguing possibility is the generation of neutrino masses and mixing via the aforementioned flavor vacuum condensate [46][47][48]. However, in the present paper we do not address the issue of the origin of neutrino masses, and focus on demonstrating the calculation of neutrino oscillations in the FTPFT framework.…”
Section: Introductionmentioning
confidence: 97%
“…Nevertheless, we adopt the approximation where the neutrino mixing is fully due to the term L Mix , that is, we neglect the residual influence of L W on the neutrino masses and mixing. Of course, we must keep in mind the caveat that not calculating these corrections misses the contributions from the vacuum condensate, which Blasone et al [46][47][48] found to be important corrections to the PMNS result. Nevertheless, they vanish in the relativistic limit, while the PMNS result is recovered [46][47][48].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation